Internalizing Islamic Character Values in Elementary Madrasah: A Multi-Site Case Study in Medan, Indonesia - Nanda Rahayu Agustia; Syamsu Nahar; Yusnaili Budianti (Al Irsyad: Jurnal Studi Islam, 2026)
Research has not yet comprehensively and empirically examined the conceptualization, internalization process, and supporting or inhibiting factors of Islamic character education through an in-depth. This study aims to comprehensively analyze the conceptualization of Islamic character education, examine its internalization process, and identify the supporting and inhibiting factors of its implementation at Madrasah Ibtidaiyah Negeri 1 Medan City and Madrasah Ibtidaiyah Negeri 7 Medan City. A qualitative, multi-site study approach was employed, using participant observation, in-depth interviews, and document analysis. Data analysis was conducted systematically and continuously through data reduction, data display, and cross-site conclusion drawing. The results indicate that Islamic character education in both madrasahs is conceptualized as an integrated educational foundation within their visions, missions, policies, curricula, and cross-disciplinary learning. Internalization is implemented through lesson planning, integration of values into the learning process, daily religious habits, teacher role modeling, and Islamic co-curricular and extracurricular activities. Continuous evaluation is carried out through observation of attitudes and student development. Supporting factors include teacher role modeling, religious leadership, madrasah culture, student motivation, and worship facilities. Inhibiting factors comprise a dense curriculum, limited instructional media, diverse parental support, administrative burdens on teachers, and the influence of technology and environment. These obstacles affect the consistency of student character building. The internalization of Islamic character education is effective because it is supported by the synergy among the madrasah, family, community, and sustainable educational policies in strengthening student character. This study reinforces the theory of Islamic character education and serves as a practical reference for madrasahs and national-level educational policymakers.